2014
DOI: 10.2323/jgam.60.175
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of heterologous thermostable cellulases in Bacillus subtilis

Abstract: Bacillus subtilis is used industrially for the production of secreted enzymes. The most characteristic feature of the secreted enzymes is variation in the N-terminal signal peptides that is recognized by secretion machinery, which is one of the determinants of efficiency and must be customized in each case. Culturing cellulolytic B. subtilis to secrete heterologous cellulases combined with customized signal peptides would be beneficial for producing biocommodities from cellulosic biomass. Four Clostridium ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Eventually, the signal peptide-cleaved proteins are transported from Golgi to the cell surface, and the mature proteins are released extracellularly. The choice of different signal peptides has been shown to significantly affect the yield of secreted proteins, including cellulases [40]. Thus, screening signal peptides is an important strategy for optimizing the secretion of heterologous proteins in bacteria and yeasts [5052].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eventually, the signal peptide-cleaved proteins are transported from Golgi to the cell surface, and the mature proteins are released extracellularly. The choice of different signal peptides has been shown to significantly affect the yield of secreted proteins, including cellulases [40]. Thus, screening signal peptides is an important strategy for optimizing the secretion of heterologous proteins in bacteria and yeasts [5052].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a total of four signal peptides were selected and used; these signal peptides can be divided into three types based on their cleavage-site motifs (Table 2): LRR/DCT of L. starkeyi amylase, VLG/AAV of L. starkeyi dextranase I and II, and VLA/APL protease of Y. lipolytica. It was reported that some customized signal peptides used for thermostable cellulase secretion have no observable effect on enzyme performance, whereas others might influence its substrate specificity in Bacillus subtilis [40]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we used mainly the (Sec dependent) signal peptide originating from the extracellular endoxylanase gtXynA (GTHT_01347; GenBank: KX962565.1) as this signal peptide was shown to be useful for hydrolytic protein secretion (Daas et al 2016;Bartosiak-Jentys et al 2013;. Recently, a library of 173 genome-derived signal peptides of B. subtilis were screened for their influence on the heterologous expression of cellulases from C. thermocellum (Thanh Bien et al 2014). It was found that these signal peptides caused negligible differences in the amounts of enzyme secreted and in their activity towards cellulose.…”
Section: Cellulolytic Activity Of Geobacillus Sppmentioning
confidence: 99%
“…Heterologous production of C. thermocellum cellulases has been demonstrated in Bacillus subtillis (Lan Thanh Bien et al 2014). Here, the production of CelK (reducing end exoglucanase; GH 9) and CelS (non-reducing end exoglucanase; GH48) was demonstrated by the clearing zones of mutant colonies on CMC plates.…”
Section: Introductionmentioning
confidence: 96%